(untitled) (Bioscience Journal, 2016)
Salt stress in rice plants affects growth, development and crop yield. However, seed treatment can reduce the deleterious effects caused by salt stress. The use of amino acids in agriculture has increased, both in Brazil and in other countries, due to higher productivity and provide better quality of plants treated with amino acids. The objective of this study was to evaluate the effect of amino acid coating on the physiological potential of rice seeds under salt stress. The experimental design was a completely randomized three-way factorial design with two batches of seeds, two levels of amino acid treatment (with or without amino acid) and five salt concentrations (0.0, 25.0, 50.0, 75.0 and 100.0 mM) with four replicates. The physiological quality of seeds was assessed by a germination test, first germination count, cold test, accelerated aging, seedling shoot and root lengths, and dry weight of shoots and roots. It is concluded that the seed treatment with amino acids results in better physiological performance of rice seeds when subjected to salt stress, which affects negatively the physiological quality of seeds.